2018
DOI: 10.4049/jimmunol.1701171
|View full text |Cite
|
Sign up to set email alerts
|

rIgG1 Fc Hexamer Inhibits Antibody-Mediated Autoimmune Disease via Effects on Complement and FcγRs

Abstract: Activation of Fc receptors and complement by immune complexes is a common important pathogenic trigger in many autoimmune diseases and so blockade of these innate immune pathways may be an attractive target for treatment of immune complex-mediated pathomechanisms. High-dose IVIG is used to treat autoimmune and inflammatory diseases, and several studies demonstrate that the therapeutic effects of IVIG can be recapitulated with the Fc portion. Further, recent data indicate that recombinant multimerized Fc molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 38 publications
5
65
0
Order By: Relevance
“…Altogether, the results reported by Spirig et al 1 could reinforce and propel the development of Fc-based therapeutics for autoimmune and inflammatory diseases. Although the Fc hexamers showed therapeutic effects in acute models of autoimmune diseases, the short half-life of this multimer and its limited mechanism of action (compared with IVIG) are major drawbacks.…”
Section: Emmanuel Stephen-victor and Jagadeesh Bayrymentioning
confidence: 76%
See 3 more Smart Citations
“…Altogether, the results reported by Spirig et al 1 could reinforce and propel the development of Fc-based therapeutics for autoimmune and inflammatory diseases. Although the Fc hexamers showed therapeutic effects in acute models of autoimmune diseases, the short half-life of this multimer and its limited mechanism of action (compared with IVIG) are major drawbacks.…”
Section: Emmanuel Stephen-victor and Jagadeesh Bayrymentioning
confidence: 76%
“…In a model of chronic arthritis, although Fc-μTP-L309C improved the clinical signs of CIA its effect waned over time and additional doses were required; by contrast, such additional therapy was not required for IVIG-treated mice 1 . Two main factors could explain these observations.…”
Section: Emmanuel Stephen-victor and Jagadeesh Bayrymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, using a series of FcγR ‐/‐ mice, we showed that the anti‐tumor activity of mAbs targeting the costimulatory molecule, CD137, are dependent on defined Fc:FcR interactions . Such observations become even more important when taken in the context of studies from others and us showing that engagement of FcRs through multimeric Fc fusion proteins—somewhat analogous to mAb opsonization of a tumor target—have the potential to induce tolerance . Collectively, these initial insights set the stage for future investigations to determine how the interplay between Fc:FcR interactions and ligation of the target molecule influence functions.…”
Section: Introductionmentioning
confidence: 76%